Implementasi K-Means Clustering Pada Sistem Pakar Penentuan Jenis Sayuran - Nur Budi Nugraha; Erna Alimudin; Bonifacius Vicky Indriyono (Journal of Innovation Information Technology and Application (JINITA), 2022)
Indramayu is one of the regencies in West Java Province that produces food crop production in the agricultural and plantation sectors. Many people work in the agricultural sector, one of which is by growing vegetables on their land. Planting vegetables on land in the Indramayu area often experiences problems, for example the land used is not in accordance with the type of vegetables grown. Some farmers have difficulty in evaluating land due to their lack of understanding of the land to be planted so that farmers rely on the system of planting habits that they usually do. The wrong land selection can result in energy and financial losses used for maintenance. Vegetables will develop imperfectly, even vegetables can die because of the inappropriateness of the land used. This study aims to assist farmers in determining what types of vegetable crops can be planted on their land using the k-means clustering method. There are 7 data criteria used for processing k-means so that later it can produce output a recommendation of vegetable types that can be planted by farmers according to the criteria they enter into the system. The results of this study produce an expert system that can provide information about vegetables selected according to the criteria selected by each user and with this system, ordinary people can find out how the selection of types of vegetables is practically on the land to be planted with vegetables.